Theory and Methods for Sociocultural Research in Science and Engineering Education - Kelly, Gregory J.; Green, Judith L. (Teaching and Learning in Science Series, 2019)
Introducing original methods for integrating sociocultural and discourse studies into science and engineering education, this book provides a much-needed framework for how to conduct qualitative research in this field. The three dimensions of learning identified in the Next Generation Science Standards (NGSS) create a need for research methods that examine the sociocultural components of science education. With cutting-edge studies and examples consistent with the NGSS, this book offers comprehensive research methods for integrating discourse and sociocultural practices in science and engineering education and provides key tools for applying this framework for students, pre-service teachers, scholars, and researchers.